Optimasi Aliran Material Handling Pada Proses Produksi Pestisida Melalui Pendekatan From To Chart (FTC) Dengan Nilai Forward-Backward Sebagai Determinan (Studi Kasus: PT. Petrokimia Kayaku–Gresik) - Dedy Kunhadi (CV. Shofanah Media Berkah, 2023)
To succeed in today's competitive business environment, companies must ensure that their facility layouts are optimized to support productivity, the latest technology, and sustainable business development. In this context, the industry plays a vital role as the primary provider of employment and driver of the economy. This research aims to enhance the efficiency of production facility layouts in the era of industry and free trade, with a focus on the Indonesian industry. A case study of PT. Petrokimia Kayaku serves as a reference in this research. The company consistently prioritizes production efficiency to meet customer demands and achieve desired targets. Therefore, this research utilizes the From to Chart (FTC) method as the primary tool to analyze and redesign production facility layouts. The research findings indicate that the second trial, A-B-C-D-F-E-G-H, with a total minimal forward and backward value of 869.647, is the better choice. By using FTC and the forward-backward approach, companies can enhance productivity and strengthen their position in an increasingly competitive market.